ETIOLOGICAL AND CLINICO-PARACLINICAL CORRELATIONS IN CASE OF CHILDREN'S ACUTE RESPIRATORY FAILURE - Iulia Armean; Cristina Oana Marginean; Lorena Elena Melit (Amaltea Medical Publishing House, 2017)
Introduction. Acute respiratory failure presents very high morbidity and mortality among the pediatric patients, being one of the most frequent causes of recurring to the emergency services and of hospitalization. Material and method. We performed a transversal retrospective study, on 153 patients diagnosed with acute respiratory failure, with the age between 2 weeks and 17 years, admitted in the Pediatrics Clinic 1 of the Emergency Clinical County Hospital Tg. Mures, between January 2015 and December 2016. Results. The ratio between genders favored the girls 1.12:1. Regarding the age, 4.57% were newborns, 32.67% were infants, 27.45% had the age between 1 and 3 years, 22.87% were preschool-aged children (4-6 years old), while 12.41% were between 7 and 17 years old. The laboratory data pointed out leukocytosis in 65.35% of the cases, neutrophilia in 70.58%, while 20.91% presented lymphocytosis, and 5.22% expressed eosinophilia. The value of C-reactive protein correlated significantly statistic with the value of erythrocyte sedimentation rate (p=0.002), and with the value of platelets (p=0.01), but not with the level of hemoglobin (p=0.15). The inflammatory biomarkers did not correlate significantly statistic with the severity of respiratory failure. The thoracic radiography pointed out pathological modifications in 75.16% of the patients, among whom 13.91% had a typical aspect of lung condensation, and 86.09% of interstitial pneumonia. In order to establish the severity of the disease, but also the patients' evolution, we calculated a prognostic score. According to this score, 10.45% had a very good prognosis, 68.62% a good prognosis and the rest of 20.93% presented a bad prognosis. Conclusions. The diagnosis of acute respiratory failure in pediatric patients presents both a complex and a multifactorial etiology